A lap joint simulant laboratory test method of aluminium alloys. Issue 12 (19th May 2015) - Zimmer, A.; Oltra, R.; Le, T. M. L.
Abstract : A lap joint simulant cavity (LJSC) with a gap thickness of 200 μm has been developed to test corrosion of assembled coated aluminium alloys. The LJSC was instrumented with electrodes allowing simultaneous pH and potential measurements in 0.5 M NaCl solution. Assuming the outer part of the LJSC is electrochemically inactive (painted sheet) it was confirmed that in free corroding conditions the pH inside the LJSC tends more towards alkalinisation. On the opposite, if the outer part of the LJSC is electrochemically active (unpainted sheet) the pH inside the LJSC tends towards an acidic value.